Fatores de proteção para o uso de drogas de abuso em uma comunidade vulnerável - Hungaro, Anai Adario (2014)
The advancement of drugs in societies and its direct and indirect, with plurality of damage to users, their families and neighborhood community, invites us to reflect on over plural forms to live and to develop more effective responses to these problems that emerge every day, whereas the presence of this phenomenon does not occur uniformly in the social space; some communities, especially the most socially vulnerable, are more exposed to drug abuse, and the impact of its use. The initiation of drug use or abuse is not by chance or by an isolated decision, but the result of multiple factors, but although there is a significant number of studies that address the risk factors to drug use, there are few of those who discuss protective factors, especially in Brazil. The objective of this research was to analyze the factors to protect the use of drugs of abuse in families in a community with high indicators of violence associated to drugs. Descriptive and cross-sectional survey using household survey and intentional sampling by reference chain and reverse, from a sequence of references provided by residents of a community with high indicators of violence associated with the use of drugs of abuse in Maringá - Paraná, considered socially vulnerable. Were interviewed 90 residents, using a semi- structured interview, complemented by a community observation guidelines and a field journal. Data collection was conducted from July to September 2014. The data were compiled in electronic data spreadsheet in Microsoft Office Excel software 10.0, where quantitative data were entered and imported into the Statistical Software Analisys for processing and data analysis. Qualitative data were analyzed by thematic content. All ethical precepts were obeyed and the participants signed the Informed Consent Statement. Respondents had an average age of 50.5 years, females - 77 (85.5 %), White color - 51 ( 56.6 %), married - 53 ( 58.9 % ) , which can be considered a protective factor, when taken into account the structured family; and predominance of incomplete primary education on - 55 (62%), below the average for the city of Maringa. The average family income was R$ 1,327.00, ranging from R$ 500.00 to R$ 7,240.00. The mean residence time in the community was 10.5 years, accompanied by recognition of the neighborhood. In family composition, 45 (50%) were nuclear families and 29 (32%) were extended families. Regarding to risk factors for the use of drugs of abuse, respondents indicated: authoritarian parents (50%), unemployment (23%), marital separation (19%), family with mental disorders (28%), family problems (11%) and domestic violence (5.6%). The employment status of respondents was wide: Retired 25 (27.7 % ), employees and self-employed 22 (24.4 %) , housewives 13 (14.4 %) and unemployed 17 (18.9 %). Social support networks of families, considered to induce protection, were found: 84 (94 %) reported activities in the community, such as study groups and church activities; the merits of friends was the neighborhood itself - reported by 67 (74.4 % ), followed by friendships in the church 38 (42.2 %) and the own extended family members 24 (26,6%) the use by people in the neighborhood did not interfere in the personal life of 58 (64.4% ) respondents; and 81 (90%) said they "could count on neighbors", confirming the inclusion/participation of a social network of trust in the community, softening the side effect of living in a socially vulnerable environment and living with trafficking and the use of drugs. As protective factors, family and religion were the main considered factors. Eighty- four residents (93.3 %) reported religion. There was predominance of the Catholic religion - 45 (50%), although the Evangelical denominations groups were reported by 28 (31.1%) families. However, when asked because they consider that their families do not use drugs of abuse , respondents pointed to protection factors related to intra-family relationships ( 83 to 92.2 % ), religion 22 (24.4 ) and other factors 49 (54.4 % ) - school , early labor activity, circle of friends, neighborhood, lack of interest and lack of contact with drugs . Referring to intra-family relations, was quoted the family education mode, the example of parents, dialogue - to talk about drugs and receive guidance and constant supervision of children. The data allow reflecting on prevention policies for problems related to drug use in our country and in our communities and guide the development of actions that address the health needs locoregional to face the epidemic of drugs of abuse.